Phage displayed domain antibody mimics for pyrethroid and its application in immunoassay - Zhao, Yanyan; Liang, Ying; Liu, Yuan; Tu, Sicong; Zhao, Shengming; Liu, Xianjin; Tu, Kang (International Journal of Agricultural and Biological Engineering, 2020)
Anti-idiotypic antibodies which can mimic antigens have many potential applications in the immunoassay. This research used the monoclonal antibody of the conserved chemical region of pyrethroids, 3-phenoxybenzoic acid (PBA), and the domain antibody library to develop an environmentally-friendly immunoassay for the detection of pyrethroids. The domain antibodies (A8, B8, and C6) which bound to anti-PBA monoclonal antibody (MAb) were isolated from a naive phage display human domain antibody library. This domain antibody is cloneable, pyrethroid-free, and applicable as a competitive mimetic antigen in the immunoassay. The best immunoassay was achieved using A8, resulting in IC50 of 0.714 μg/mL for PBA, 1.775 μg/mL for Cypermethrin, 1.624 μg/mL for β-cypermethrin, 3.675 μg/mL for Fenvalerate, and 4.895 μg/mL for Flucythrinate. This way of selecting anti-idiotypic antibodies to detect pyrethroids could provide potential applications in developing immunoassays for identifying various chemical contaminants in food. Keywords: domain antibody, enzyme-linked immunosorbent assay, phenoxybenzoic acid, pyrethroid DOI: 10.25165/j.ijabe.20201302.5492 Citation: Zhao Y Y, Liang Y, Liu Y, Tu S C, Zhao S M, Liu X J, et al. Phage displayed domain antibody mimics for pyrethroid and its application in immunoassay. Int J Agric & Biol Eng, 2020; 13(2): 235–240.